MRI-based insights into brain structural and functional alterations in schizophrenia treated with risperidone - Li, Hangyu; Chen, Xinyue; Peng, Shiji; Li, Ying; Yu, Rui; Liao, Kaike; Liu, Nian (Frontiers in Psychiatry, 2025)
BackgroundSchizophrenia (SZ) is a severe psychiatric disorder, with antipsychotics serving as the primary treatment. Among them, risperidone plays a crucial role in alleviating both positive and negative symptoms while also enhancing cognitive function. Advances in magnetic resonance imaging (MRI) technology have provided an effective means of investigating the effects of risperidone on the brain, particularly in terms of neural pathways, therapeutic efficacy, and predictive outcomes. This review offers a summary of current findings on the impact of risperidone treatment on gray matter, white matter, and functional brain activity and connectivity in SZ patients, including its neural mechanisms, therapeutic benefits, and potential side effects.MethodsLiteratures on the use of risperidone for treating schizophrenia were searched in PubMed, Embase and Web of Science analyzing and summarizing the alterations in brain structure and function associated with risperidone.ResultsThrough the analysis and summary, it was found that risperidone treatment in SZ patients can have a marked effect on different structural and functional regions including the prefrontal lobe, temporal lobe, cingulate gyrus, corona radiata, basal ganglia, and corpus callosum.ConclusionMost research has focused on short-term effects, with limited longitudinal data to assess long-term efficacy and side effects, more researches could be added in the future. In addition, more potential methods such as DKI, DSI and brain covariance network have the opportunity to be used in the study of brain structure and function in the treatment of schizophrenia with risperidone in the future.